(untitled) (Homoeopathy for All, 2023)
The field of homeopathy has long been regarded as a holistic and alternative approach to healthcare, focusing on the individual as a whole rather than simply treating symptoms. Homeopathic physicians possess a deep understanding of the intricate dynamics between the human body, mind, and spirit, and their expertise in this domain serves as a strong foundation for further academic pursuits. While a career in homeopathy offers immense opportunities for personal and professional growth, many individuals with a background in homeopathy are now considering the option of pursuing a PhD in various subjects, differing from the core subjects of the field, to complement their existing knowledge.